2019
DOI: 10.1175/jcli-d-19-0137.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics and Large-Scale Environments of Mesoscale Convective Systems East of the Rocky Mountains

Abstract: The spatiotemporal variability and three-dimensional structures of mesoscale convective systems (MCSs) east of the U.S. Rocky Mountains and their large-scale environments are characterized across all seasons using 13 years of high-resolution radar and satellite observations. Long-lived and intense MCSs account for over 50% of warm season precipitation in the Great Plains and over 40% of cold season precipitation in the southeast. The Great Plains has the strongest MCS seasonal cycle peaking in May–June, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
183
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(213 citation statements)
references
References 71 publications
13
183
0
Order By: Relevance
“…Similar results obtained using the NLDAS and Stage IV precipitation datasets and agreement of the MCS rainfall characteristics with those discussed in previous studies (e.g., Feng et al, 2019;Nesbitt & Zipser, 2003;Song et al, 2019) lend confidence to our conclusions. Although the trends examined here are based on data from only 22 years, our findings align well with projected changes in precipitation in a warming climate-precipitation becomes more extreme and more variable.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Similar results obtained using the NLDAS and Stage IV precipitation datasets and agreement of the MCS rainfall characteristics with those discussed in previous studies (e.g., Feng et al, 2019;Nesbitt & Zipser, 2003;Song et al, 2019) lend confidence to our conclusions. Although the trends examined here are based on data from only 22 years, our findings align well with projected changes in precipitation in a warming climate-precipitation becomes more extreme and more variable.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Although we limit our examples to the mature stages in the MCS lifecycle, any lifecycle assessment based on the presence of key radar squall‐line precipitation properties is nonetheless nontrivial to generalize. Moreover, we anticipate that mature MCS transition from updraft‐dominant to downdraft‐dominant phases, for example, as reflected by changes in mature‐stage convective and stratiform precipitation coverage (e.g., Feng et al, 2019). Thus, the authors recommend caution when interpreting the mature‐stage results that follow.…”
Section: Core Results Within Mature Mcs Convective Linesmentioning
confidence: 99%
“…Previous studies show that the MMF with the coarse host‐GCM grid is able to capture MCSs in the Tropics (Tao & Chern, ; Randall et al, ). However, our study shows the MMF model has difficulty in simulating MCS‐associated precipitation in midlatitude continental conditions during spring where most MCSs were supported by strong baroclinic forcing (Feng et al, ; Song et al, ). The different model behaviors reflect the different mechanisms driving the MCSs between tropical and midlatitude regions.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…Investigating how resolving topography variations within the CRM domains would help the MMF model simulate MCSs can be an interesting future work. Further, summer MCSs in this region often occur under weak baroclinic forcing with favorable thermodynamic environments (Feng et al, ; Song et al, ). Future work similar to this study is needed to examine how well the MMF can simulate observed summer MCSs.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation